K virom Prešernovega "frajgajstovstva" - Paternu, Boris (Slavistična revija, 2009)
The article examines one of the intellectual sources of Prešeren's free-spritedness that has not been previously considered, i.e. Thomas Paine (1730-1809), who was and inspiration to the American and French revolutions. Prešeren had it in his modest personal library Paine's most important work, Right of Man (Volume 1 from 1791). Here, he could have come in contact with a universal treatment of the question of human rights on the individual as well as on national and international levels. He became familiar with the legal culture of modern democracy. One can identify numerous common points in Prešeren's and Paine's ideas, most notably in Prešeren's Zdravljica Toast.
Keywords: 19.st.; Paine, Thomas, 1737-1809; Prešeren, France, 1800-1849; Prešeren, France: Zdravljica; Slovene literature; slovenska književnost; slovenska poezija